Respuesta :
Step-by-step explanation:
use formula
(-b+√b2-4ac)/2a
a=3, b=2 , c=5
(-2+√4-4×3×5)/2×3
(-2+√-56)/6
(-2+2√-14)/6
(-2 +2√14i)/6
The quadratic equation has a form of
[tex]ax^2+bx+c=0\wedge a\neq0[/tex]
We have
[tex]3x^2+2x+5=0[/tex]
Hence our coefficients are
[tex]a=3,b=2,c=5[/tex]
Now to find a solution we have to look at the equation, since equation has no apparent solution given by the factorisation we are forced to use quadratic formula.
[tex]x_{1,2}=-\dfrac{b^2\pm\sqrt{b^2-4ac}}{2a}[/tex]
Put in the data and simplify a bit
[tex]
x_{1,2}=-\dfrac{2^2\pm\sqrt{2^2-4\cdot3\cdot5}}{2\cdot3} \\
x_{1,2}=-\dfrac{4\pm\sqrt{-56}}{6}\in\mathbb{C}
[/tex]
And we get two complex solutions
[tex]
x_1=\boxed{-\dfrac{4}{6}-\dfrac{56}{6}i} \\
x_2=\boxed{-\dfrac{4}{6}+\dfrac{56}{6}i}
[/tex]
Hope this helps.
r3t40